Digitalization – Implementation - Jereb, Borut (Digital Transformation in Logistics and Supply Chain Management, 2026)
Software is intangible, and its creation is still associated with individuals in the digitization of processes. As software has become highly complex, organizations developing and using it face new opportunities and challenges throughout its entire life cycle. ISO/IEC 12207:2011 is a standard that provides a framework for describing the life cycle of software systems based on an interdisciplinary approach. The software life cycle encompasses processes from conception to development or acquisition, through testing, deployment, maintenance, and eventual retirement. Understanding the life cycle helps all stakeholders establish systematic and organized management of software-related work, which is crucial for improving quality and reducing issues in the digitization of business processes. Software quality, crucial for user satisfaction, is reflected in functionality, reliability, performance, usability, maintainability, portability, security, and scalability. ISO/IEC 25010:2017 is a standard defining a comprehensive quality model, enabling the assessment and improvement of software.